Women, social justice & human rights - Gupta, Vijay Kumar ([S.l.] : MD Pub Pvt Ltd, 2009)
Women all over the world-in villages, corporations and governments are stepping forward to claim their rightful roles as leaders. Human rights of a woman mean her liberation from the traditional oppressive bonds and discrimination, improvement in the concept of self and her in relation to the environment and the people around her.In terms of analysis and strategy, social justice feminism consistenly promotes an approach to women's issues that integrates race, class, sexuality, nationality, citizenship, age, ability and other markers of social inequity. It recognizes and challenges the operations of power and privilege, both in the broader society and within the women's movement itself and while pursuing an agenda that centres on the styatus and well being of women, social justice feminism actively challenges racism, heterosexist bias, and class privilege. The present volume analyses on social justice to women and their human rights and makes serious contributions to Law, Human Rights, Social Welfare, Social Work, Sociology participatory research and public administration.
Keywords: India; Social justice; Women's rights; Women--Social conditions